The Effect of Discovery Learning Model on Basic Science Process Skills and Science Learning Outcomes of Class Vi Students at SDIT Al Madinah Maros - Affandi, Ahmad; Nurlina, Nurlina; Ma’ruf, Ma’ruf (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
The rapid development of science and technology demands an increase in basic science process skills (KPS) and student learning outcomes, especially in science education. This study aims to examine the effect of discovery learning model on KPS and science learning outcomes of grade VI students at SDIT Al Madinah Maros. This study used a quantitative approach with a quasi-experimental design involving control and experimental groups without random selection (nonequivalent control group design). Data were collected through validated observation sheets and analyzed using the MANOVA statistical test. The results showed that the discovery learning model had a significant effect on improving students' KPS and learning outcomes compared to the conventional learning method. This finding indicates that discovery learning is effective in improving students' critical thinking skills and conceptual understanding. The implications of this study support the application of the discovery learning model in the broader context of science education to develop better process skills and learning outcomes. However, further research with more diverse samples and more comprehensive measurement methods is needed to strengthen the generalizability of these findings.